(3efLO GdebQFjf heQTO GdWGdHjfs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,J (B833 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdGeGe GeG HYO MeOkG ddg GdPi NdbfG bGd GHh GdbGSe GdgOdi SCd eGdc QVi Gddg Yfg abGd GdSfI GdLgQ HgG s
(3BNQgG (B:s
(3ajMJed GfgG Jchf YfOge eJhGJQI GP de jUd EdjfG NHQge hgPG YLH hGddg GYde s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1859s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs